Features of the Clinical Course of Urinary Stone Disease in the Farming Population (Global Journal of Medical Research, 1970)
In the climatic conditions of the Fergana Valley of Uzbekistan, 2478 people aged 18-70 engaged in farming were studied in a one-time epidemiological study. Questionnaire, clinical, biochemical, instrumental and special urological examination methods were used. The clinical symptoms of urolithiasis are determined to have a number of specific features, including risk factors and comorbidity. Severe urolithiasis and exacerbation of symptoms are observed in patients with a risk factor of 12.8 times, and in the presence of comorbidity - up to 45.7%.
Keywords: farmer population; urolithiasis; clinical course; risk factors; epidemiology; comorbidity